(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Around the 8th-9th century, language, art, literature, culture, and the Bengali nation emerged. Along with the progress of the Bengali nation, its own classical and folk art and culture paved the way. In the modern (post-colonial) era, the folk art and culture of Bengal has gained considerable recognition in international folk culture circles. The popular Odia Deity and aslo Bengali Deity lord Jagannath appears in various guises in the multifaceted style of Bengali folk (Lokāyata) art. The idols (Vighraha) of Lord Jagannath are made of different material. These idols made of various materials have been used for worship as well as for decorating the house. The folk or Lokāyata artists of Bengal have given beauty to the idols of Jagannath with their infinite patience and skill. The folk or Lokāyata artists of Bengal have used wood, clay, cloth, thread, paint, metal, conch etc. This work has brought economic success to folk or Lokāyata artists. The Jagannath cult has now become one of the most popular genres in Bengal’s folk art or Lokayata-art.